Innovation Ped in the Process of Improving the Methodology of Chorus and Chorology. The Role of Technologies - Khodjaeva Lily Latipova (Peerian Journals Publishing, 2022)
This article outlines the theoretical basis for the use of multimedia technologies to highlight theoretical aspects of chorus and chorology, as well as music culture. It also highlights the process of organizing classes through multimedia technologies.
Keywords: music education; multimedia; technology; methodology